Achieving β-phase poly(vinylidene fluoride) from melt cooling: Effect of surface functionalized carbon nanotubes - Ke, Kai; Poetschke, Petra; Jehnichen, Dieter; Fischer, Dieter; Voit, Brigitte (Polymer, 2014)
Poly(vinylidene fluoride) (PVDF) based nanocomposites with different surface-functionalized multi-walled carbon nanotubes (MWCNTs) were prepared by melt mixing in a small scale compounder. With the incorporation of commercial functionalized MWCNTs, the β-phase in PVDF can be directly achieved from melt cooling, as verified by results of Fourier transform infrared spectrum and X-ray diffraction. Interestingly, nanocomposites with amino group functionalized MWCNTs showed the highest percentage of β-phase (17.4%) formation in PVDF, followed by those with hydroxyl groups (11.6%) and unmodified MWCNTs (9.4%). However, the nanocomposites containing MWCNTs with carboxyl groups which were thought to be able to well interact with the dipoles on PVDF chains have the lowest amount of β-phase, i.e. 4.7%. The analysis on the mechanism of the influence of surface functionalization of MWCNTs on the formation of β-phase in PVDF shows that the combined effects of the dispersion of MWCNTs and the nanotube-polymer interactions account for the formation of the β-phase in PVDF.© 2013 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Multi-walled carbon nanotubes (MWCNTs); Poly(vinylidene fluoride) (PVDF); β-phase